1999
DOI: 10.1063/1.123430
|View full text |Cite
|
Sign up to set email alerts
|

Onset of blistering in hydrogen-implanted silicon

Abstract: The onset of surface blistering in hydrogen-implanted single crystalline silicon was studied. A combination of atomic force microscopy and optical measurements shows that hydrogen-containing platelets grow laterally below silicon surface until they suddenly pop up as surface blisters due to the internal hydrogen pressure after a critical size has been reached. Experimentally and theoretically, the critical size of the onset blisters was found to increase with increasing implantation depth or top layer thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 8 publications
4
36
0
1
Order By: Relevance
“…[15] It was found that in order for LaAlO 3 (100) to achieve blistering and layer splitting with an H 2 + dose of 3.5±5.0´10 16 /cm 2 H implantation must be performed on a wafer in the temperature range~450 tõ 550 C. For the LaAlO 3 samples that were implanted by H 2 + at 450 C at an H 2 dose of 5´10 16 /cm 2 at 160 keV the blistering time as a function of annealing temperature is given in Figure 14. Again, an Arrhenius relation is observed and the activation energy is about 1.7 eV.…”
Section: Laalo 3 Layer Transfermentioning
confidence: 97%
“…[15] It was found that in order for LaAlO 3 (100) to achieve blistering and layer splitting with an H 2 + dose of 3.5±5.0´10 16 /cm 2 H implantation must be performed on a wafer in the temperature range~450 tõ 550 C. For the LaAlO 3 samples that were implanted by H 2 + at 450 C at an H 2 dose of 5´10 16 /cm 2 at 160 keV the blistering time as a function of annealing temperature is given in Figure 14. Again, an Arrhenius relation is observed and the activation energy is about 1.7 eV.…”
Section: Laalo 3 Layer Transfermentioning
confidence: 97%
“…13 This mechanism, driven by increases in the partial pressure of hydrogen and helium in cavities and microvoids combined with the elastic energy of the solid in the vicinity of cracks, is similar to the layer transfer mechanism which has now been widely observed in semiconductor materials. 14 Figure 1(a) is a polarized-optical micrograph illustrating the domain structure of a transferred BaTiO 3 layer on a Pt-coated substrate. The domain structure in the film is seen to be strikingly similar to that of the unimplanted bulk BaTiO 3 crystal.…”
mentioning
confidence: 99%
“…Microcracks can occur within the platelet when trapped H 2 gas becomes pressurized at higher temperatures. This cracking expands by growth or coalescence with other microcracks up to a critical size where physical separation occurs within the lattice [6]. Figure 1 shows a simplified drawing of a platelet containing a gas inclusion.…”
Section: Results and Discussion; Process Optimization In Simentioning
confidence: 99%